iPhone User Interface Design Projects - Barnard, David (Apress, 2012)
This is a book about user interface design. As a consequence, you’ll find lots of screenshots and only very little code. Several of the authors don’t even have a programming background, but they all share the same passion for the iPhone and for developing apps of the highest standards in terms of user experience. David Barnard of App Cubby is one such person; he has created a suite of essential utilities that enjoy great popularity on the App Store. In Chapter 1, he takes you through the process of perfecting entry views and presenting data, which both play central roles in his apps. And he explains how learning from Apple’s UI conventions and usability testing can improve your final result. In Chapter 2, I make an attempt to enhance the user experience and power of the navigation bar and present a relevant subset of large amounts of data in an exciting way. I bring you along on the same journey I took myself, as I actually came up with the design while I was writing the chapter. Former Apple employee and Yellow Dog Linux distributor, Dan Burcaw talks on going native with his social networking app, Brightkite, in Chapter 3. He covers how that move made it possible to add the extra umph with CoreLocation, Camera, and Address Book integration that web apps just don’t have. And, equally importantly, he explains how he tailored the user interface to match his target group.